PENGARUH KUALITAS LAYANAN, KEPERCAYAAN, DAN NILAI NASABAH TERHADAP KEPUASAN NASABAH TABUNGAN PADA BANK MAYBANK UNIT KUDUS - Dera Apriliyanto Putra, 12.05.51.0101 (Students' Journal of Economic and Management, 2017)
The purpose of this research was to analyze the influence of service quality, trust and customer value on customer satisfaction of PT. Maybank Unit in Kudus. The population in this research was the saving customers of Maybank unit in Kudus. The sample was in this research as many as 100 people. The sampling technique used was purposive sampling. The criteria of the sample in this research was the saving customers of Maybank unit in Kudus who were saving active lasted for at least 3 months. The analysis method used was multiple linear regression. It can be concluded that the service quality, trust and customer value affected positive influence on customer satisfaction. Keywords: Service Quality, Trust, Customer Value and Customer Satisfaction